WOMEN AGAINST THE RAJ : The Rani of Jhansi Regiment - Lebra, Joyce, 1925- (Institute of Southeast Asian studies, 2008)
This is a ground-breaking history of the Rani of Jhansi Regiment, part of the Indian National Army led by Bengali revolutionary Subhas Chandra Bose during World War II. The Regiment, a hitherto forgotten part of 'the Forgotten Army', was composed largely of teenage volunteers from Malayan rubber estates, girls who had never seen India yet were eager to enlist to liberate India from colonial bondage. Bose, creator of the Regiment, connected a historical thread extending from the original Rani of Jhansi, killed in battle by the British in 1858, through Bengali women revolutionaries of the 1930s, to the Regiment, which he hoped would spearhead the liberation of India. The ""Rani of Jhansi Regiment"" provides a model of empowerment relevant for contemporary Indian women.